Photodegradation of Bisphenol A with ZnO and TiO2: Influence of Metal Ions and Fenton Process - An, Seong-Nam; Choi, Nag-Choul; Choi, Jae-Woo; Lee, Soonjae (Kluwer Academic Publishers, 2018)
In this study, photocatalytic degradation of bisphenol A (BPA) was investigated using two types of catalysts (TiO2 and ZnO) with various metal ion concentrations and amounts of added H2O2. A kinetic test was performed to observe the changes of BPA over time under UV irradiation in a photocatalytic reactor. Experimental results demonstrated that degradation efficiency of ZnO was higher than that of TiO2. The degradation rate increased as catalyst dosage increased until reaching optimum dosage, after which degradation rate decreased. The addition of H2O2 improved the degradation efficiency of BPA, with the degradation efficiency increasing with the amount of H2O2. All metal ions, including Fe2+, Ni2+, and Cu2+, inhibited the degradation of BPA by ZnO at natural pH, whereas Fe2+ and Ni2+ enhanced degradation efficiency of BPA at acidic pH. Comparison of BPA degradation with H2O2 only, ZnO/H2O2, Fe2+/H2O2, and ZnO/Fe2+/H2O2 revealed that Fe2+/H2O2 was more efficient than other processes at lower pH (pH = 3.44), whereas ZnO/H2O2 the most efficient at higher pH (pH = 6.44). These results indicate that ZnO/H2O2 process was observed to be the most efficient of all processes. Degradation efficiency of BPA by ZnO was also influenced by additional parameters, including H2O2 concentration, metal ions, and solution pH.